Hepatic bile acid accretion correlates with cholestatic liver injury and therapeutic response in Cyp2c70 knockout mice with a humanized bile acid composition - Klindt-Morgan, Caroline; Truong, Jennifer K.; Bennett, Ashley L.; Pachura, Kimberly J.; Herebian, Diran; Mayatepek, Ertan; Luedde, Tom; Ebert, Matthias; Karpen, Saul J.; Dawson, Paul A. (American journal of physiology. Gastrointestinal and liver physiology, 2024)
Download figureDownload PowerPoint